COLLABORATION AND ACHIEVEMENTS OF STUDENTS MOTIVATION IN PHYSICS LEARNING - Siregar, Ramadana Fitrah (Universitas Negeri Medan, 2021)
Teaching and learning activities that tend to be monotonous and passive result in low student interest in learning and achievement. Therefore, this study aims to determine the collaboration and achievement of student motivation in learning physics. This research is applied with the cooperative learning model Group Investigation (GI) type in six phases that can improve collaboration, motivation and student achievement, namely selecting topics, cooperative planning, implementation, analysis and synthesis, presentation, evaluation. This type of research is a quasi experiment. The instrument used was a test of student learning outcomes in the form of descriptions totaling 10 items and student activity sheets, namely experimental activities. The results showed that the existence of good peer collaboration will affect the achievement of student motivation in learning physics.